Korean pricing policies and economic development in the 1960s - Brown, Gilbert T. (Baltimore, John Hopkins University Press, 1973)
This book dwells much on eight years involvement in Korean economic policy problems and development from the early 1963 - 1971
Includes bibliographical index
mf 24/01/2019
Loans
Keywords: Prices; Korea (South); Korea (South)